1987
DOI: 10.1155/lc.8.39
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Absorption Spectroscopy of Polymethine Cis‐Trans Isomerization

Abstract: Results are presented of time resolved fluorescence and absorption investigations of DDEOCI (3,3'-diethyl-6,6'-diphenyl-9-ethyl-oxacarbocyanine iodide) in solvents which differ in polarity and viscosity. The measured picosecond absorption and fluorescence kinetics probed at various wavelengths of the polymethine dye studied can be fitted to a double exponential decay with a minor fast component of lifetime τ1 and a major slower component of lifetime τ2. Furthermore, probing in the S1←S0 absorption region and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…J-aggregates of polymethine dyes have become a focus of interest in the interdisciplinary field of molecular nonlinear optics [1][2][3][4][5] and Langmuir-Blodgett engineering [6][7][8]. Polymethine dye J-aggregates were formed in LB layers, and storage of optical information in mono-*Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…J-aggregates of polymethine dyes have become a focus of interest in the interdisciplinary field of molecular nonlinear optics [1][2][3][4][5] and Langmuir-Blodgett engineering [6][7][8]. Polymethine dye J-aggregates were formed in LB layers, and storage of optical information in mono-*Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…All-trans isomers (usually considered the most stable ground state conformation of polymethine dyes) are excited vertically to the first excited state, which further relaxes via two competitive channels: fluorescence and rotation around the double bond. On the S 1 potential surface, the all-trans and 90° conformations are separated by an energy barrier of less than few tens of kJ/mol [38]. The molecule quickly overcomes the barrier and reaches the potential minimum of the 90° conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, cis isomers thermally revert to the initial trans form, which is the favoured direction of the ground state isomerization in cyanine dyes [25]. Alternatively, it has been suggested that in some cases moderately stable twisted species can exist in the ground state, corresponding to an extra shallow energy minimum on the S 0 surface [37,38]. The absorption spectra of cyanine cis or twisted isomers strongly overlap with those of trans isomers and usually are bathochromically shifted [39].…”
Section: Introductionmentioning
confidence: 99%